Patterned Magnetic Pole Configurations in Bonded Magnets - Behera, Malaya Prasad; Lv, Yifan; Singamneni, Sarat (Nature Portfolio, 2026)
Additive manufacturing of bonded magnets using polymer extrusion, powder bed fusion, and stereolithography is established, but this paper focuses on the laser powder bed method. Magnetic particles mixed with polymer powders were consolidated into bonded magnets by selective laser sintering. External magnetic fields were applied to align particles during sintering, but with uniform powder compositions and fields, the effects of which were limited to bulk properties. Considering the point-wise material consolidation mechanics, we hypothesise that controlled dispersion of multiple powder materials and localised external magnetic fields in specific orientations and at specific times during sintering can lead to bonded magnets with controlled magnetic heterogeneity. Results from experimental research conducted and reported in this paper have shown this hypothesis to be true. The outcome of this research paves ways towards achieving bonded magnets with controlled placement of different magnetic materials. The as-printed samples exhibit relatively weak polarisation (≈ 1.5-2 mT flux), but magnetisation under external fields (1.5-1.9 T) raises flux values up to 6 mT N / 3 mT S for NdFeB/FeSi and 14 mT N / 6 mT S for NdFeB/FeCo, demonstrating strong amplification of polar strengths. Both NdFeB/FeSi and NdFeB/FeCo samples show 80-100 mT North and 50-100 mT South differential polarities under external fields, with minimal change from as-printed to magnetised states. Even when the external field is reversed, a persistent North-upward remanent tendency confirms an easy-axis alignment induced during laser consolidation.
Keywords: Bonded magnets; Controlled magnetism; Laser sintering; Multi-materials; Multi-polar; 4014 Manufacturing Engineering; 40 Engineering